Automated wrapping machine/ Ammar Arham, Azulaifiz Fauzan Aznam, Mohd Noor Halmy Ab Latif and Norshadila Ahmad Badela - Arham, Ammar; Aznam, Azulaifiz Fauzan; Ab Latif, Mohd Noor Halmy; Ahmad Badela, Norshadila (School of Mechanical Engineering, 2023)
The product wrapping process at Jalen Sdn Bhd factory were carried manually, where the workers will hold the wrapper and move around the cartons of products one by one. Limitations occurs when the product produced excessively, where the wrapping process it will consume much time and energy. The main objectives of this project are to develop a machine that reduce the use of manpower and minimize time for wrapping. The body of the machine is fabricated using an aluminium profile with a size of 40mm x 40 mm which involved the process of cutting and drilling. It is then assembled by using aluminium L bracket using bolt and screw. A motor is used to create the rotation for the wrapping process. A roller is attached to the body to smoothen the machine movement. The time taken to complete the wrapping process using the machine is 1 minutes while manual wrapping process is 4 minutes. The number of manpower required is 1 compared to manual wrapping which is 2. In conclusion, the objectives for this project were achieve successfully as it able to reduce the time taken and numbers of manpower for the wrapping process.